Results from the Survey of Antibiotic Resistance (SOAR) 2002-09 in Turkey - (:unkn) unknown (OXFORD UNIV PRESS, 2016)
Objectives: To investigate changes in antibiotic susceptibility of Streptococcus pneumoniae and Haemophilus influenzae from the Survey of Antibiotic Resistance (SOAR) in community-acquired respiratory tract infections (CA-RTIs) between 2002 and 2009 in Turkey. Methods: Previously published SOAR data were used for this analysis. MICs were determined using Etest (R) gradient strips or disc diffusion. Susceptibility against a range of antimicrobial agents was assessed using CLSI breakpoints. Results: A total of 900 S. pneumoniae isolates were analysed: 2002-03 (n = 75), 2004-05 (n = 301) and 2007-09 (n = 524). Four antibiotics were tested consistently throughout and three showed a statistically significant decrease in susceptibility (P < 0.0001): penicillin (74.7% susceptible in 2002-03; 67.8% in 2004-05; and 47.2% in 2007-09); cefaclor (85.3% in 2002-03; 78.7% in 2004-05; and 53.5% in 2007-09) and clarithromycin (85.3% in 2002-03; 82.7% in 2004-05; and 61.9% in 2007-09). Susceptibility to amoxicillin/clavulanic acid did not significantly change (100% in 2002-03; 98.7% in 2004-05; and 97.7% in 2007-09). A total of 930 H. influenzae isolates were analysed: 2002-03 (n = 133), 2004-05 (n = 379) and 2007-09 (n = 418). Four anti-biotics were also consistently tested: ampicillin, amoxicillin/clavulanic acid, clarithromycin and cefaclor. All showed >90% susceptibility, but only cefaclor susceptibility significantly reduced (P<0.0001) over time (99.2% in 2002-03; 96.3% in 2004-05; and 90.4% in 2007-09). Conclusions: In S. pneumoniae from Turkey, there has been a clear statistically significant reduction in susceptibility to key antibiotics since 2002, but not to amoxicillin/clavulanic acid (or amoxicillin). However, susceptibility in H. influenzae remained stable. Continued surveillance is required to monitor future changes in antibiotic susceptibility for CA-RTI bacteria.
Keywords: COMMUNITY-ACQUIRED PNEUMONIA; STREPTOCOCCUS-PNEUMONIAE; OTITIS-MEDIA; ANTIMICROBIAL RESISTANCE; PATHOGENS; CHILDREN; BURDEN; MANAGEMENT; EUROPE